Development of methodology for evaluation and real water loss reduction in water supply systems in transition countries - Orašanin Goran S.; Ristić Dragana S.; Vlaški Dalibor; Vučijak Branko S. (Tehnika, 2014)
Key strategy for water supply companies, aiming increasing their capacity and expanding the network, should be to focus on reducing water losses and non revenue water in general. Water loss reduction, after conveniently achieving initial progress, requires continuous efforts to maintain or improve the achieved level of water losses. This paper proposes a methodology developed on the basis of collected and analyzed knowledge and experience gained in water utilities in BiH and neighboring countries. The methodology is also based on the experiences presented in the literature relating to water losses in developed countries, which are applicable or adaptable, so as affordable for the countries in transition.